2014
DOI: 10.1021/jp504096d
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Ion Effects on the Polarization of Metal-Bound Water and Infrared Vibrational Modes of the Coordinated Metal Center of Mycobacterium tuberculosis Pyrazinamidase via Quantum Mechanical Calculations

Abstract: Mycobacterium tuberculosis pyrazinamidase (PZAse) is a key enzyme to activate the pro-drug pyrazinamide (PZA). PZAse is a metalloenzyme that coordinates in vitro different divalent metal cofactors in the metal coordination site (MCS). Several metals including Co2+, Mn2+, and Zn2+ are able to reactivate the metal-depleted PZAse in vitro. We use quantum mechanical calculations to investigate the Zn2+, Fe2+, and Mn2+ metal cofactor effects on the local MCS structure, metal–ligand or metal–residue binding energy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 88 publications
(155 reference statements)
0
14
0
Order By: Relevance
“…Catalytic proteins may contain metal ions providing functional properties, such as coordination ability and redox activity. A specific ligand’s combination with the surrounding hydrogen bonding system has a central metal‐like redox potential …”
Section: Methodsmentioning
confidence: 99%
“…Catalytic proteins may contain metal ions providing functional properties, such as coordination ability and redox activity. A specific ligand’s combination with the surrounding hydrogen bonding system has a central metal‐like redox potential …”
Section: Methodsmentioning
confidence: 99%
“…This is due partly to the growing interest in MM‐ and QM/MM‐type computer simulations of nonbiological molecular systems such as metal–organic frameworks (MOFs), which could sometimes go beyond the chemical space covered by existing parameter sets. In addition, even for biological systems, parameterization is necessary when a metal ion or some other cofactor is involved …”
Section: Introductionmentioning
confidence: 99%
“…From 200 ns simulations, we revealed that the wild type remained stable, whereas in the mutant form (G97D), the protein destabilized signicantly. AS reported earlier that the Fe 2+ ion inuences the catalysis of this enzyme activity; [45][46][47][48][49] however, mutations can alter these activities. In the current research, novel mutations (F94L, F94S, G97C, G97D, G97S, K96N and K96R) in the pncA gene are shown to have a metal ion effect (Fe 2+ ) on PZase, which is likely to inuence the enzyme activity associated with the conversion of PZA into POA.…”
Section: Discussionmentioning
confidence: 99%